2004
DOI: 10.1207/s15324796abm2703_5
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally appropriate sexual risk reduction interventions for adolescents: Rationale, review of interventions, and recommendations for research and practice

Abstract: Context-Despite awareness of the need to design developmentally-appropriate sexual risk reduction interventions for adolescents, limited information exists to identify the aspects of intervention design or content that make an intervention "developmentally appropriate." Objectives-(a)To clarify the rationale for designing developmentally-appropriate interventions, (b) to review randomized controlled trials (RCTs) of adolescent sexual risk reduction interventions, (c) to identify developmentally-appropriate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
156
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 66 publications
7
156
0
1
Order By: Relevance
“…In our study, greater perceived pregnancy consequences were associated with higher contraceptive use levels only among older teens. That contraceptive use levels were not associated with perceived pregnancy consequences in younger teens may reflect differences in cognitive development, with younger teens less likely to link current behaviors with potential future consequences [31]. Higher perceived STD/HIV risk was associated with lower levels of contraceptive use only among 10-11 th grade girls, suggesting that older adolescent girls who are not using dual methods may make realistic assessments of their STD/HIV risk [32].…”
Section: Discussionmentioning
confidence: 90%
“…In our study, greater perceived pregnancy consequences were associated with higher contraceptive use levels only among older teens. That contraceptive use levels were not associated with perceived pregnancy consequences in younger teens may reflect differences in cognitive development, with younger teens less likely to link current behaviors with potential future consequences [31]. Higher perceived STD/HIV risk was associated with lower levels of contraceptive use only among 10-11 th grade girls, suggesting that older adolescent girls who are not using dual methods may make realistic assessments of their STD/HIV risk [32].…”
Section: Discussionmentioning
confidence: 90%
“…Peer influences may have been particularly salient in the current study because 64% of SHERO's participants reported that they always came to the sessions with their friends. The potentially positive influence of peers is supported by reviews of existing HIV prevention interventions, which have shown that perceived norms and social connectedness are key factors in successful interventions for adolescents (Kirby, 2001;Pedlow & Carey, 2004), as well as findings from friendshipbased HIV prevention interventions that utilize the power of peer norms to support positive behavior change (Dolcini et al, 2008;Stanton et al, 1996). Forthcoming manuscripts will conduct more in-depth moderation and mediation analyses to further explore the effects of such psychosocial outcomes (e.g., peer norms, perceptions of a woman's control of her sexuality, acceptability of sexual coercion and assault) on sexual health-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of school-based sex education programs do not address the concerns and questions of many YMSM (6), and data suggest that YMSM are less likely to receive school-based sex education at all (7) despite their desire for it (8). In fact, four recent reviews that identified more than 60 published articles on randomized controlled trials or quasi-experimental studies on HIV risk reduction interventions for adolescents (~age < 19) failed to find one effective intervention targeted at YMSM (9)(10)(11)(12). A recent meta-analysis of HIV behavioral interventions targeting MSM similarly did not find a single RCT where the mean age was less than 23 (13) and the CDC's HIV/AIDS Prevention Research Synthesis Team recently concluded that there is a significant gap in HIV prevention programs targeting YMSM (14).…”
mentioning
confidence: 99%